Permainan Engklek dalam Meningkatkan Konsentrasi dan Keterampilan Sosial Anak Tunagrahita Ringan - Sismala Harningtyas; Susanti, Nanik; Irsyadi, Taris (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
Children with mild intellectual disability (ID) typically have an IQ ranging between 50 and 70. They retain the capacity to learn basic reading, writing, and arithmetic, and can adapt to social life with appropriate guidance. However, they frequently experience difficulties in concentrating, comprehending abstract concepts, and completing complex tasks. Consequently, they require specialized education and therapy to ensure their potential is developed optimally.  This study aims to determine the effect of the engklek traditional game on improving concentration and social skills in children with mild intellectual disability. The community service activities employed explanation and Q&A sessions, demonstration and re-demonstration, followed by evaluation. The traditional game of engklek was found to enhance both concentration and social skills in children with mild intellectual disabilities.  The engklek game has a positive influence on improving the concentration and social skills of children with mild intellectual disability. Through the activity of playing engklek, children are trained to focus on game rules, regulate their movements precisely, and sustain attention throughout the activity. This process was proven effective in increasing their concentration ability. Furthermore, Engklek also provides opportunities for children to interact with peers, learn to wait their turn, cooperate, and adhere to group rules. These activities help enhance children's social skills in communication and socialization. Therefore, the engklek game can be utilized as an enjoyable and effective learning method for improving the concentration and social skills of children with mild intellectual disability in special education settings.